The happy isles of Oceania : paddling the Pacific - Theroux, Paul. (London : Penguin Books, 1992)
Describes the exotic adventures of the author as he kayaks from island to island in the Polynesian Pacific.
Adult
Keywords: Theroux, Paul -- Travel -- Polynesia; Theroux, Paul -- Travel; Kayaking; Oceania -- Description and travel; Polynesia -- Description and travel